Utilization of sugarcane bagasse cellulose for producing cellulose acetates: novel use of residual hemicellulose as plasticizer - Shaikh, Hamid M.; Pandare, Kiran V.; Nair, Greeshma; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
Sugarcane bagasse was fractionated to cellulose, hemicellulose and lignin by a proprietary steam explosion process, followed by downstream purifications, developed in our laboratory. The fractionated cellulose contained similar to 94% cellulose, about similar to 5% hemicellulose, traces of lignin (similar to 0.2%), and similar to 1% ash. The cellulose was acetylated under heterogeneous conditions to obtain cellulose acetates. These were extensively characterized using FTIR, TGA, DSC, GPC, HPIC, WAXRD, and viscometry. The novel feature of this study was the utilization of the hemicellulose content (5%) of bagasse cellulose as an internal plasticizer. Through kinetic experimentation, we have demonstrated that the residual hemicellulose need not be considered as an impurity; rather it can be used in acetylated form as a plasticizer as well as a biodegradable additive for cellulose acetates made from slightly impure cellulose produced from non-wood origin. Our results therefore show how lignocellulosic agricultural wastes can be utilized to produce high value plastics. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bagasse cellulose; Cellulose acetate; Hemicellulose; Plasticizer; Sugarcane bagasse; Xylan acetate

Efficient conversion of cellulose to levulinic acid by hydrothermal treatment using zirconium dioxide as a recyclable solid acid catalyst - Joshi, Sunil S.; Zodge, Amit D.; Pandare, Kiran V.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2014)
Conversion of cellulose into platform chemicals is essential for sustainable development of the chemical industry. With this aim, single step hydrothermal conversion of cellulose to industrially important levulinic acid using zirconium dioxide as a catalyst has been investigated. A remarkably high yield (53.9 mol %) of levulinic acid with excellent accountability and total conversion of cellulose has been achieved at 180 degrees C reaction temperature and reaction time of 3 h with 2 wt % of catalyst and 2 g of cellulose. The major products identified were levulinic acid (LA), formic acid (FA), 5-hydroxymethylfurfural (5-HMF), furfural, and humins. Formation of humins during cellulose hydrolysis and dehydration was observed and is also confirmed by NMR and FTIR analysis. The effect of various reaction parameters such as temperature, time, substrate concentration, and catalyst loading on conversion and selectivity has been studied. The catalyst has been regenerated and recycled several times without any loss of activity and selectivity.